Effects of a 12-week walking intervention on circulating lipid profiles and adipokines in normal weight and abdominal obese female college students - Yi-Han Chiu; Shiow-Chwen Tsai; Chen-Si Lin; Li-Yu Wang; Kuo-Chin Huang (Elsevier, 2023)
Background/Objectives: Regular exercise such as aerobic exercise has been shown to reduce the risk of some diseases such as cardiovascular disease (CVD). However, only few studies have investigated the impact of regular aerobic exercise on non-obese and overweight/obese persons. Therefore, this study was designed to compare the effect of a 12-week 10,000 steps a day walking intervention on the body composition, serum lipids, adipose tissue function, and obesity-associated cardiometabolic risk between normal weight and overweight/obese female college students. Methods: Ten normal weight (NWCG) and 10 overweight/obese (AOG) individuals were recruited in this study. Both groups performed a regular 10,000 steps a day walk for 12 weeks. Their blood pressure, body mass index, waist-to-hip ratio, and blood lipid profiles were evaluated. Moreover, serum leptin and adiponectin levels were measured using an enzyme-linked immunosorbent assay. Results: Our results revealed that triglyceride (TG), TG/high-density lipoprotein cholesterol (HDL-C) ratio and leptin were significantly reduced in the AOG group after the 12-week walking intervention. However, total cholesterol, HDL-C, and adiponectin/leptin ratio were significantly increased in the AOG group. There was little or no change in these variables in the NWCG group after the 12-week walking intervention. Conclusions: Our study demonstrated that a 12-week walking intervention may help improve cardiorespiratory fitness and obesity-associated cardiometabolic risk by decrease resting heart rate, modulating blood lipid profiles, and inducing adipokine alterations in obese individuals. Therefore, our research encourages obese young adults to improve their physical health by participating in a 12-week walking program of 10,000 steps a day.